2015
DOI: 10.1007/s11010-015-2556-2
|View full text |Cite
|
Sign up to set email alerts
|

Antioxidant action of six Trifolium species in blood platelet experimental system in vitro

Abstract: This study includes a comparative evaluation of antioxidant effects of plant extracts (1.5–50.0 μg/ml), derived from six clover (Trifolium) species: T. alexandrinum L., T. fragiferum L., T. hybridum L., T. incarnatum L., T. resupinatum var. majus Boiss., and T. resupinatum var. resupinatum L. Chemical profiles of the extracts contained three or four groups of (poly)phenolic compounds such as phenolic acids, clovamides, isoflavones, and other flavonoids. Antioxidant properties of Trifolium extracts were assesse… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
5
0

Year Published

2016
2016
2021
2021

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(5 citation statements)
references
References 56 publications
0
5
0
Order By: Relevance
“…A comparative in‐vitro analysis of free radical scavenging properties of extracts from other Trifolium species demonstrated that several clovers might be a source of potent antioxidants. On the other hand, the mentioned works confirmed the importance of individual components for the total antioxidant efficacy of plant extracts.…”
Section: Antioxidant Activitymentioning
confidence: 99%
See 2 more Smart Citations
“…A comparative in‐vitro analysis of free radical scavenging properties of extracts from other Trifolium species demonstrated that several clovers might be a source of potent antioxidants. On the other hand, the mentioned works confirmed the importance of individual components for the total antioxidant efficacy of plant extracts.…”
Section: Antioxidant Activitymentioning
confidence: 99%
“…Additionally, both clovers (T. repens and T. campestre) displayed moderate cytotoxic effects (LC50 between 30 and 50 lg/ml) against the brine shrimp. [86] A comparative in-vitro analysis of free radical scavenging properties of extracts from other Trifolium species [87][88][89] demonstrated that several clovers might be a source of potent antioxidants. On the other hand, the mentioned works confirmed the importance of individual components for the total antioxidant efficacy of plant extracts.…”
Section: Antioxidant Activitymentioning
confidence: 99%
See 1 more Smart Citation
“…14 Plants from this genus have been utilized in the treatment of chronic skin diseases and menopausal symptoms. 15 In addition, species from this genus have been employed as a phytoestrogen source, 16 antioxidants, 17,18 anti-inflammatories 19 and in antidiabetic treatment. 20 Previous phytochemical investigation showed that the genus Trifolium contains flavonoids, isoflavonoids, chalcones, terpenes and coumarins.…”
Section: Introductionmentioning
confidence: 99%
“…In organic extracts of T. subterraneum, Tava et al (2019) found only low amounts of phenolic compounds (glycosyl derivatives of caffeic acid, and ferulic and coumaric acids), and Oleszek et al (2007) described high concentrations of isoflavonoids and low concentration of phenolic acids and flavonoids. The last authors and Kolodziejczyk-Czepas et al (2015) found shallow total contents of phenolic acids and high amounts of flavonoids -specifically, apigenin and luteolin derivatives (Zgórka, 2011)-in organic extracts of T. incarnatum. These findings are consistent with ours, whereas naringenin and prunetin had not been reported in T. subterraneum until now.…”
Section: Accepted Papermentioning
confidence: 93%